Cancer stem cell in breast cancer therapeutic resistance. (September 2018) - Bai, Xupeng; Ni, Jie; Beretov, Julia; Graham, Peter; Li, Yong
Highlights: Breast cancer stem cells (BCSCs) set the stage for breast cancer metastasis and recurrence after several years. The potential of surface markers for BCSC identification, separation, and targeting is discussed. Central signaling pathways associated with BCSCs are promising targets. The challenges for BCSCs therapy needs to be overcome. BCSC-targeted drug delivery system and differentiation therapy represent an efficient way to eradicate BCSCs. Abstract: Development of therapeutic resistance and metastasis is a major challenge with current breast cancer (BC) therapy. Mounting evidence suggests that a subpopulation of cancer stem cells (CSCs) contribute to the cancer therapeutic resistance and metastasis, leading to the recurrence and death in patients. Breast cancer stem cells (BCSCs) are not only a consequence of mutations that overactivate the self-renewal ability of normal stem cells or committed progenitors but also a result of the de-differentiation of cancer cells induced by somatic mutations or microenvironmental components under treatment. Eradication of BCSCs may bring hope and relief to patients whose lives are threatened by recurrent BCs. Therefore, a better understanding of the generation, regulatory mechanisms, and identification of CSCs in BC therapeutic resistance and metastasis will be imperative for developing BCSC-targeted strategies. Here we summarize the latest studies about cell surface markers and signalling pathways that sustain the stemness of BCSC and discuss the associations of mechanisms behind these traits with phenotype and behavior changes in BCSCs. More importantly, their implications for future study are also evaluated and potential BCSC-targeted strategies are proposed to break through the limitation of current therapies.